Power System Dynamics and Stability (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The characteristics of power electronics in the safe and stable operation of power systems have been a trend in the research of new power systems, and this reprint focuses on research related to the modeling of power electronic systems and the study of dynamic stability mechanisms. This reprint contains research on modeling the dynamics and stability of power electronic systems, spanning many subject areas. It includes power electronic power systems, analysis of the power electronic power system simulation method, power electronic power system oscillation analysis and suppression measures, power electronic power system oscillation control method, and other topics.